2010
DOI: 10.4103/0377-4929.72030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high-risk human papillomavirus types 16 and 18 in healthy women with cytologically negative pap smear in Iran

Abstract: The prevalence of high-risk HPV was highest in the youngest women and gradually decreased with age. Overall, the prevalence of HPV in our population is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 1 publication
2
12
0
Order By: Relevance
“…In the present study, HPV 16 and 18 DNA was found in 62.7% and 30.2% of the women, respectively, which is not surprising because the majority of women between 50-59 years of age have been shown to test positive for these HPV types (28). In this study, HPV 16 and 18 DNA was found in the majority of the older women between 30-50 years of age, and this finding is also in agreement with the results of other studies (29,30).…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, HPV 16 and 18 DNA was found in 62.7% and 30.2% of the women, respectively, which is not surprising because the majority of women between 50-59 years of age have been shown to test positive for these HPV types (28). In this study, HPV 16 and 18 DNA was found in the majority of the older women between 30-50 years of age, and this finding is also in agreement with the results of other studies (29,30).…”
Section: Discussionsupporting
confidence: 69%
“…HPV DNA was identified in 5.7% women who were admitted to different hospitals and gynecological clinics in Tehran [13]. Safaei et al [14] reported positive HPV findings in 5.5% of women who were examined at two gynecological clinics in Shiraz, a city in the southwest of Iran with a population very similar to the population in the current study. Therefore, it seems that the prevalence of HPV infection was very similar in different gynecological clinics in Iran and was comparable to other geographical areas in Muslim and Middle Eastern countries.…”
Section: Discussionmentioning
confidence: 52%
“…Most epidemiological data for HPV infection comes from cross-sectional studies with samples taken from women in different hospitals and gynecological clinics [8-14]. These women had cervical neoplasia or cancer [8-10], abnormal cervical cytology [11-13], and normal Pap smears [10,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to studies applying cytological or DNA-based methods for identification of HPVs among healthy women, the rates of HPV types 16 and 18 in the present study were relatively high. Previously, Khodakarami et al from Tehran in 2011, Zandi et al from Bushehr in 2010, and Safaei et al from Shiraz in 2010 reported that the prevalence of HPV types 16 and 18 among healthy Iranian women ranged from 2% -3.1% and 0% -1.5%, respectively (22)(23)(24). Beyond the HPV genotyping methods, different explanations may exist for such differences between our results and those of the mentioned studies, for example the number of asymptomatic patients in our study population.…”
Section: Discussionmentioning
confidence: 99%